Our stories, ourselves : the emBODYment of women's learning in literacy - Miller, Mev; King, Kathleen P., 1958- (Emerald Publishing Limited : Information Age Publishing, 2011)
Women's lives are often written on our bodies. Yet very little is made of the impacts of embodiment for women in literacy education, both learners and professionals. This volume presents the writings of 26 contributors--teachers, students, and administrators--who examine the rich terrain of personal and professional experiences related to whole person engagement in learning and teaching. These writings provide a compass to guide readers through the bodily landscapes, mindful flights, willful spirits, and emotional embraces.Written with the same desire to open minds, hearts and practices to new understanding, this book builds on the successful style of Empowering Women through Literacy (2009). This new volume appeals to all readers, as the essays, poems, and investigations woven through its pages challenge us to consider the embodyment of women's learning. Join us on the journey as we travel across many arenas and discover significant ways to comprehend and support best practices in teaching and learning, especially for women.
Keywords: Women -- Education (Continuing education) -- United States.; Literacy programs -- United States.; Sex differences in education -- United States.; Body image.; Education -- Adult & Continuing Education.; Adult education, continuous learning.; elektronické knihy; electronic books